Diagnostic challenges in cervical tuberculous lymphadenitis: A review - Deveci, Hande Senem (North Clin Istanb, 2016)
Tuberculosis is a very serious disease and incidence is once again on the rise. Lymph node tuberculosis is one of the most common extrapulmonary manifestations of tuberculosis. In differential diagnosis of chronic, painless cervical lymphadenopathy, cervical tuberculous lymphadenitis should be kept in mind. A high index of suspicion is needed for diagnosis of tuberculous lymphadenitis, which is known to mimic a number of pathological conditions. This article reviews epidemiology, clinical manifestations, and diagnostic techniques for cervical tuberculous lymphadenitis.